Pitfalls of PTOs in land ownership and control: Rethinking access for rural development in South Africa - Chitja Twala; Hope Luke Vhiga (Interdisciplinary Journal of Rural and Community Studies)
Permission to Occupy (PTOs) was viewed by the apartheid regime as an important mechanism for addressing inequalities in South Africa (SA). The African National Congress (ANC) government has ruled over SA for the past 30 years but has been unsuccessful in dealing with the country’s racialised land inequalities. The land reforms introduced by the ANC government have not addressed the challenges of land in the country in a timely manner. Thus, tackling the issue of land inequalities remains crucial. A desktop review was conducted to critically examine the pitfalls of PTOs in the context of rural development and advocates for a re-evaluation of access mechanisms to promote more equitable and sustainable land tenure systems. The results show that these pitfalls perpetuate socio-economic inequalities, hinder investment in land improvements, and contribute to conflicts over land resources. In response, the article proposes alternative approaches to enhance access to land for rural development, such as community-driven land governance mechanisms, participatory land-use planning, and the recognition of customary land tenure systems. These alternative strategies prioritise rural local empowerment, strengthen tenure security, and foster inclusive decision-making processes.